Modelling of DSTATCOM for distribution system. (3rd January 2006) - Singh, Bhim; Adya, Alka; Mittal, A.P.; Gupta, J.R.P.
This paper deals with the simulation of distribution static synchronous compensator (DSTATCOM) for improving power quality of a distribution system feeding linear as well as non-linear loads. Nowadays, there are an increasing number of non-linear loads which inject harmonics into the system. A three-phase insulated gate bipolar transistor- (IGBT-)based current controlled voltage source inverter with a DC bus capacitor known as a DSTATCOM is used for power factor correction, harmonic compensation and for providing required reactive power to the load. A model of DSTATCOM connected to a power distribution system feeding linear and non-linear loads (diode bridge rectifier with R and R-C) is developed for predicting the behaviour of system under transient conditions. Simulation is carried out in standard MATLAB environment using Simulink and power system blockset toolboxes. Control algorithm is made flexible so that it can correct supply power factor, eliminate harmonics and provide load balancing. The control algorithm utilises one closed loop PI controller for regulating the DC link voltage of DSTATCOM and second PI controller for regulating the AC voltage at point of common coupling. Results are presented for a variety of linear and non-linear balanced as well as unbalanced loads, which demonstrate power factor correction, voltage regulation, harmonic elimination and load balancing capabilities of DSTATCOM.